2006
DOI: 10.1163/156853806778189981
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the Patagonian lizard Phymaturus patagonicus

Abstract: The growth dynamics of Phymaturus patagonicus, a diurnal, herbivorous and viviparous lizard from the Argentinean Patagonian steppe, was studied using eight juveniles (two born in the laboratory), 11 adult females and eight adult males. Histological cross sections of femoral bones were analysed to determine if individuals show osseous growth marks and if these marks provide useful age estimates. Individual ages were assessed after estimating the reabsorbed rings in relation to snout-vent length. There was a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 19 publications
(30 reference statements)
3
30
1
1
Order By: Relevance
“…In the studied population, the relationship between age and SVL is statistically significant. Similar results have been recently reported for some other lizard species (P. patagonicus, Piantoni et al, 2006;D. mosorensis, Tomašević et al, 2010;L.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the studied population, the relationship between age and SVL is statistically significant. Similar results have been recently reported for some other lizard species (P. patagonicus, Piantoni et al, 2006;D. mosorensis, Tomašević et al, 2010;L.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the SVL mean of females did not significantly differ from that of males, although the latter were bigger on average. Similar to our results, no statistically significant difference between the sexes was reported in the studies of Eremias multiocellata (Li et al, 2006), Phymaturus patagonicus (Piantoni et al, 2006), Lacerta agilis (Guarino et al, 2010), and Eremias argus (Kim et al, 2010). In contrast to our study, the SVL mean of females was significantly larger than that of males in Sceleporus undulatus (Haenel and John-Alder, 2002) and Lacerta vivipara (Liu et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Although a lifespan of up to 12 years or more could sound overstated for a medium-sized lizard, other lizard species located at high elevations are also known to be long-lived. For example, a skeletochronology study suggested that one adult female from a 60-70 mm cohort of the viviparous L. multicolor Koslowsky, 1898 was 19 years of age (Valdecantos et al 2007), and Phymaturus patagonicus Koslowsky, 1898 (SVL = 88.0-109.0 mm) can live up to 16 years (Piantoni et al 2006). However, for L. multicolor the authors suggest caution since that specific finding might be an outlier and not accurately represent what occurs within the remaining sample.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, bone grows by an appositional process of surface deposition (Enlow 1963, Piantoni et al 2006, Arakelyan et al 2013, Çiçek et al 2015. Bone growth occurs when the subject is active and resources are available for its development (Adolph and Porter 1993, Castanet 1994, Valdecantos et al 2007, Comas et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation